HDAC6 inhibition: a significant potential regulator and therapeutic option to translate into clinical practice in renal transplantation - Zhang, Qian-qian; Zhang, Wei-jie; Chang, Sheng (Frontiers in Immunology, 2023)
Histone deacetylase 6 (HDAC6), an almost exclusively cytoplasmic enzyme, plays an essential role in many biological processes and exerts its deacetylation-dependent/independent effects on a variety of target molecules, which has contributed to the flourishing growth of relatively isoform-specific enzyme inhibitors. Renal transplantation (RT) is one of the alternatively preferred treatments and the most cost-effective treatment approaches for the great majority of patients with end-stage renal disease (ESRD). HDAC6 expression and activity have recently been shown to be increased in kidney disease in a number of studies. To date, a substantial amount of validated researches has identified HDAC6 as a pivotal modulator of innate and adaptive immunity, and HDAC6 inhibitors (HDAC6i) are being developed and investigated for use in arrays of immune-related diseases, makng HDAC6i a promising therapeutic candidate for the management of a variety of renal diseases. Based on accumulating evidence, HDAC6i markedly opens up new avenues for therapeutic intervention to protect against oxidative stress-induced damage, tip the balance in favour of the generation of tolerance-related immune cells, and attenuate fibrosis by inhibiting multiple activations of cell pro-fibrotic signaling pathways. Taken together, we have a point of view that targeting HDAC6 may be a novel approach for the therapeutic strategy of RT related complications, including consequences of ischemia-reperfusion injury (IRI), induction of immune tolerance in transplantation, equilibrium of rejection, as well as improvement of chronic renal graft interstitial fibrosis after transplantation in patients. Herein, we will elaborate on the unique function of HDAC6, which focuses on therapeutically mechanism of action related to immunological events with a general account of the tantalising potential to the clinic.